2009
DOI: 10.1002/dmrr.919
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin‐like growth factor‐I and its binding proteins in glucose homeostasis and type 2 diabetes

Abstract: Summary This review addresses the possible role of the insulin-like growth factor (IGF)-axis in normal glucose homoeostasis and in the etiopathogenesis of type 2 diabetes. IGF-I, a peptide hormone, shares amino acid sequence homology with insulin and has insulin-like activity; most notably, the promotion of glucose uptake by peripheral tissues. Type 2 diabetes as well as pre-diabetic states, including impaired fasting glucose and impaired glucose tolerance, are associated cross-sectionally with altered circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
167
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(185 citation statements)
references
References 172 publications
12
167
0
6
Order By: Relevance
“…Individually, the different components of the metabolic syndrome have most often been shown to be associated with low IGF1 values (27,28,29,30,31,32,33). In this study, when investigated as dichotomous variables, only the component of high triglycerides was associated with IGF1 concentrations.…”
Section: Discussionmentioning
confidence: 61%
“…Individually, the different components of the metabolic syndrome have most often been shown to be associated with low IGF1 values (27,28,29,30,31,32,33). In this study, when investigated as dichotomous variables, only the component of high triglycerides was associated with IGF1 concentrations.…”
Section: Discussionmentioning
confidence: 61%
“…The IGF-1R is commonly overexpressed in many cancers, including NSCLC, and IGF-1 and IGF-2 link to IGF-1R leading the consequent activation of intracellular signaling pathways, then affecting cancer cell proliferation, adhesion, migration and are critical for cancer cell survival and metastases (LeRoith et al, 2003). What's more, the insulin-like effects of IGF-1 via IGF-1R played a crucial part in the maintenance of normal glucose homeostasis and may contribute to the etiopathogenesis of type 2 diabetes (Rajpathak et al, 2009). In our study, higher IGF-1R expression was found in NSCLC with preDM, which is supported by previous study reported by Rosalyn Ferguson whose study found that, in conditions of hyperinsulinemia, there was the higher phosphorylation of IR/IGF-1R which contributed to the increased growth of mammary tumors (Ferguson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The biology of the IGF system is complex, consisting of ligands (IGF-I and IGF-II) and the cognate receptors (IGF-IR and IGF-IIR) in addition to six IGF-binding proteins (IGFBPs), and plays an important role in cell growth and proliferation [13,14]. IGF-I shares structural homology with insulin and, like insulin, promotes the peripheral uptake of glucose and fatty acids [15].…”
Section: Igf Systemmentioning
confidence: 99%